Bad Impression Of Heavy Metal Culture Reflected In Metal: A Headbanger's Journey Directed By Sam Dunn (2008):A Sociological Approach - Arifin, Rosyid; , Drs. Abdillah Nugroho, M.Hum; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed (2013)
The main aim of this study is to find out how Bad impression of heavy metal culture is reflected in Sam Dunn's Metal: A Headbanger's Journey by correlating its structural elements and social historical background of America in early twenty first century. Indeed, literature and sociology are bounded each other due to the assumption that the appearance of literary work is in social emptiness. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Sam Dunn's Metal: A Headbanger's Journey while secondary data sources are other sources related to the primary data. Data collecting method is library research and in analyzing the data the researcher employs descriptive analysis. The outcomes of this study show the following conclusions. Firstly, it analyzes the structural element of the movie. Secondly, based on sociological analysis, the movie reveals that there are some reasons underlying bad impression of society towards heavy metal culture. Social aspect deals with the social condition of America in early twenty first century. Political aspect discusses about the PMRC as the political organization that has censorship against heavy metal. Economic aspect deals with how metalhead work together to keep their metal industry alive. Religious aspect focuses the religion in American and impression of heavy metal that considers as satanic ang blashphemous. Cultural aspect discusses three aspect of culture, namely mental, behavioral and physical fact. Science and technology explains how internet and radio as the media to introduce heavy metal in society.